2019
DOI: 10.21009/jobbe.003.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Fan Identification, Brand Community Identification, and Oppositional Brand Loyalty towards Sponsors of a Rival Sports Team: The Mediating Role of Schadenfreude

Abstract: Empirical evidence confirms that brand loyalty is broadly understood in the context of positive side i.e. supportive loyalty compared to negative side i.e. oppositional loyalty. However, theoretically positive (supportive) loyalty cannot be explained exclusively without considering negative (oppositional) loyalty. This study, therefore, examines brand loyalty using a triadic approach combining both negative and positive loyalty in the cycle of love and hate relationship. Specifically, the study examined the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This result is a reflection of the misconception that increasing fanaticism on social media will increase the degree of OBL, and so clubs must take into account to adopt good behavior towards the content posters created by the club in a way that limits the negative effects of the phenomenon of sport fanaticism. At the same time, this study is an extension of previous studies that investigated the role of fans' behavior in OBCs in general (e.g., Al-Thunayan, 2014;Ashour, 2020;Dalakas & Melancon, 2012;Hickman & Ward, 2007) and with OBL towards sponsors of a rival club in specific (e.g., Amani, 2019;Dessart et al, 2015;Kumar & Nayak, 2019;Olson, 2018;Popp et al, 2016;Ramírez et al, 2019;Xiabing et al, 2015).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This result is a reflection of the misconception that increasing fanaticism on social media will increase the degree of OBL, and so clubs must take into account to adopt good behavior towards the content posters created by the club in a way that limits the negative effects of the phenomenon of sport fanaticism. At the same time, this study is an extension of previous studies that investigated the role of fans' behavior in OBCs in general (e.g., Al-Thunayan, 2014;Ashour, 2020;Dalakas & Melancon, 2012;Hickman & Ward, 2007) and with OBL towards sponsors of a rival club in specific (e.g., Amani, 2019;Dessart et al, 2015;Kumar & Nayak, 2019;Olson, 2018;Popp et al, 2016;Ramírez et al, 2019;Xiabing et al, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, OBL is participant of the OBCs who refuse or resist suggestions for usage brands from competitor companies (Ewing et al, 2013). As a result, OBL is a psychological phenomenon in which a person expresses appreciative behavior toward his or her preferred brand while displaying hostile conduct toward competitors or rival brands (Amani, 2019). Participants who have OBL have a high level of commitment to their preferred brand, as well as a deliberate resistance and animosity towards rival brands (Kuo & Hou, 2017).…”
Section: Oppositional Brand Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…Schadenfreude refers to the malicious pleasure when competing brands or customers of competing brands encounter misfortune [35]. Previous research showed that confrontational loyalty hurts competitive teams' sponsors, and schadenfreude has a moderating effect on confrontational loyalty, community identification, and fan identification [17].…”
Section: A Oppositional Loyaltymentioning
confidence: 99%
“…Confrontational loyalty behaviors between competing brands are also widespread in other industries, including beverages [10], smartphones [11], [12], automobiles [13], [14], video cards, microprocessors [15], fashion, sports, tourism, media, entertainment [16], football clubs [17], and online games [18]. Notably, in the mobile internet environment, it is easy for individual confrontational behaviors to escalate to group antagonistic behaviors [19], [20], producing a more comprehensive range of influences.…”
Section: Introductionmentioning
confidence: 99%